Differential Use of Human Neutrophil Fcγ Receptors for Inducing Neutrophil Extracellular Trap Formation - Omar Rafael Alemán; Nancy Mora; Ricarda Cortes-Vieyra; Eileen Uribe-Querol; Carlos Rosales (Journal of Immunology Research)
Neutrophils (PMN) are the most abundant leukocytes in the blood. PMN migrate from the circulation to sites of infection, where they are responsible for antimicrobial functions. PMN use phagocytosis, degranulation, and formation of neutrophil extracellular traps (NETs) to kill microbes. NETs are fibers composed of chromatin and neutrophil-granule proteins. Several pathogens, including bacteria, fungi, and parasites, and also some pharmacological stimuli such as phorbol 12-myristate 13-acetate (PMA) are efficient inducers of NETs. Antigen-antibody complexes are also capable of inducing NET formation. However the particular Fcγ receptor involved in triggering this function is a matter of controversy. In order to provide some insight into what Fcγ receptor is responsible for NET formation, each of the two human Fcγ receptors was stimulated individually by specific monoclonal antibodies and NET formation was evaluated. FcγRIIa cross-linking did not promote NET formation. Cross-linking other receptors such as integrins also did not promote NET formation. In contrast FcγRIIIb cross-linking induced NET formation similarly to PMA stimulation. NET formation was dependent on NADPH-oxidase, PKC, and ERK activation. These data show that cross-linking FcγRIIIb is responsible for NET formation by the human neutrophil.